2004
DOI: 10.1021/la036249m
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Surface Properties of Porous Nanometric Zirconia Particles by Covalent Grafting

Abstract: We here report on the covalent grafting of various phosphated species (phosphoric acid, phenylphosphonic acid, and octyl phosphate) onto the surface of monoclinic zirconia nanoparticles obtained by hydrothermal treatment of zirconium acetate. The initial particles are 60 nm aggregates of nanometric primary grains and present an inner porosity. Small-angle X-ray scattering shows that the high specific area of the colloidal particles (450 m2·g-1) decreases to 150 m2·g-1 upon drying. Therefore, phosphated reactan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 32 publications
(39 reference statements)
3
40
0
Order By: Relevance
“…Moreover, if necessary, the alumina coating is readily dissolvable in basic media, providing access to superparamagnetic anisometric nanoparticles with a surface primarily composed of iron oxide. On the other hand, zirconia interacts strongly with phosphate compounds, [9] and in fact has been used as a highly selective adsorbent for compounds containing phosphonic acid. [10] Consequently, it is reasonable to expect high stability and functionality once the zirconia coating has been grafted with phosphate moieties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, if necessary, the alumina coating is readily dissolvable in basic media, providing access to superparamagnetic anisometric nanoparticles with a surface primarily composed of iron oxide. On the other hand, zirconia interacts strongly with phosphate compounds, [9] and in fact has been used as a highly selective adsorbent for compounds containing phosphonic acid. [10] Consequently, it is reasonable to expect high stability and functionality once the zirconia coating has been grafted with phosphate moieties.…”
mentioning
confidence: 99%
“…Finally, it is worth noting that electrophoretic mobility measurements indicate that SPNRs coated with alumina are positively charged at physiological pH. In contrast, a simple protocol ([H 3 PO 4 ] ¼ 0.1 M, 4 h at 100 8C) [9] has been used to successfully graft zirconia-coated SPNRs with phosphate moieties. In summary, we have shown that a relatively simple approach can be used to prepare anisometric superparamagnetic iron oxide nanoparticles despite the inherent difficulties associated with shape anisotropy.…”
mentioning
confidence: 99%
“…We have recently proposed the use of zirconia matrixes because of their high stability at different pHs and high reactivity with phosphate compounds. [110] Zirconia easily reacts with phosphate compounds, [111] and in fact is used as a highly selective adsorbent for compounds containing phosphonic acid. [112] Titania matrixes could also be considered a good replacement to silica, especially because they can impart photocatalytic properties to the SPCs.…”
Section: Discussionmentioning
confidence: 99%
“…After 12 h of heating detectable traces neither of 5 nor of 5' were found in solutions corresponding to a 20 wt % loading. The CP-MAS 31 P NMR spectrum of 5@ZS 20 C showed two large main peaks at d = 3.5 and 54 ppm, which were ascribed to the phosphonate moiety [17] and to the phosphine, respectively. Interestingly, the second chemical shift (d = 54 ppm) is shifted significantly downfield relative to that recorded for the free ligand (d = À9 ppm).…”
Section: Synthesis Of the Grafted Materialsmentioning
confidence: 98%